Implementation of Character Education Management in The Learning Process in Junior High Schools - Mogonta, Sirra; Wullur, Mozes M.; Lengkong, Jeffry SJ (Abdurrauf Science and Society, 2025)
This study aims to analyze and describe: 1) Planning of character education management in the learning process at Kawangkoan National Junior High School. 2) Implementation of character education management in the learning process at Kawangkoan National Junior High School. 3) Results of the implementation of character education management in the learning process at Kawangkoan National Junior High School. This study uses qualitative research with a field research approach that is described descriptively which attempts to describe phenomena or relationships related to the application of moral values ??through character education management in fostering students' morals at Kawangkoan National Junior High School. The results of the study illustrate that the planning of character education management in the learning process at Kawangkoan National Junior High School is carried out regularly and integrated by referring to the school's vision and mission and the values ????of Pancasila. The implementation of character education management in the learning process at Kawangkoan National Junior High School aims to instill strong moral and ethical values ??in students, through structured management. Kawangkoan National Junior High School integrates character values ??into all aspects of learning both in and out of class. The results of the implementation of character education management in the learning process at Kawangkoan National Junior High School show a positive impact on students' attitudes and behavior.